Improved ablation resistance and thermal insulation performances of polyimide composites by introducing albite/glass powder composition. (14th February 2022) - Xu, Qinging; Li, Yunhui; Zeng, Fanming; Zhang, Yifan; Deng, Pengyang; Su, Zhongmin
Polyimide is a class of resins with high heat resistance, and their composites have a wide range of applications in military and civilian. However, the application of polyimides as an ablation and thermal insulation material has always been a challenge due to their low char yield during ablation in the air. Herein, we described the first application of polyimide composites—albite/glass powder doped polyimide hybrid materials - as an ablation and thermal insulation material. The key to the success of this case is that the process of the ceramization of albite/glass powder can greatly reduce the carbon loss of polyimide during the ablation process in the air. Moreover, the mechanical properties, thermal stability, ablation and thermal insulation properties of these polyimide hybrid materials have been studied systematically. This work not only opens up a new application for polyimide, but also provides a new idea for the design of novel ablation and thermal insulation material.